ANALISIS PERENCANAAN SUMBER DAYA MANUSIA (SDM) KESEHATAN PUSKESMAS DENGAN METODE WORKLOAD INDICATORS OF STAFFING NEEDS (WISN) DI KABUPATEN LOMBOK BARAT - Ni Wayan Sri wangi (Master of Management, Mataram University, 2017)
This research is aimed at analyzing health human resources in health centers by calculating the work load, need number and competence of each unit and category of health human resourcesof health centers and the need of the development in West Lombok. This research is descriptive study with quantitative and qualitative approach. Quantitative data are analyzed with Workload Indicators of Staffing Needs (WISN). Qualitative data are analyzed with Miles and Huberman through the analysis of organization, work, and personal needs. The sample of health center and informants were selected through purposive sampling method. The selected samples are Gunung Sari Health Center and Meninting Health Center. All 168 health staffs are respondents and 10 of which are the informants of this research. The data were collected through documentation, questionnaires, in-depth interview, and focus group discussion (FGD). The reseach showed that 8 work units and 8 categories of health staff in Gunung Sari Health Center and 7 work units and 7 categories of health staff in Meninting Health Center have the high ratio of work load (WISN ratio <1). Low work load ratio (WISN ratio >1) are in 4 categories of health staff in Gunung Sari Health Center and 1 unit and 4 categories of health staff in Meninting Health Center. Gunung Sari Health Center needs 114 staffs, and only 98 are alvailable, so it need 16 more additional staffs. Meninting Health Center needs 87 staffs, and only 70 are alvailable, so it need 17 more additional staffs. The analysis of human resource development showed that nurses need to be upgraded into Diploma III, training for emergency action, diagnostic test to support doctor. Management training is needed by trasurer and good procurement staff. Training of service administration is needed by all staffs of health center. This research recommend that health center make planning for staff recruitment, inter-unit rotation, and health human resources development as recommended by WISN analysis and health center development need in West Lombok. Keywords: workload, WISN, health human resources development need, health center